2014
DOI: 10.17547/kjsr.2014.22.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Communication Apprehension and Performance of Using Communication Skills according to Nursing Students' Enneagram Personality Types

Abstract: The purpose of study was to identify Communication apprehension & performance of using communication skills according to nursing students' Enneagram personality types. With a descriptive survey design, a self report study was conducted 291 nursing students. The research tools of this study were Korean enneagram personality types, personal report communication apprehension, performance of using communication skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…선행연구들을 살펴보면, 간호대학생을 대상으로 에니어그램 성격유형, 우울 및 불안과의 관계 (Lee, 2007), 에니어그램 성 격유형에 따른 의사소통 불안과 의사소통기술 수행의 차이 확인 (Park & Ha, 2014), 에니어그램 성격유형에 따른 건강증 진행위의 차이를 파악한 연구 (Kim, 2014)등이 있다. 그리고 대인돌봄행위 연구에서 간호대학생을 대상으로 정서지능과 대 인돌봄행위간에 유의한 상관관계 확인 (Peak, 2013), 대인돌봄 행위가 자아존중감과 정신건강, 희망, 삶의 질을 향상시키는 효과 확인 (Choi & Lee, 2010), 임상간호사의 대인돌봄 행위 수준 확인과 대인돌봄행위를 제공한 후의 효과 (Son, 2012) 연구의 구체적인 목적은 다음과 같다.…”
unclassified
“…선행연구들을 살펴보면, 간호대학생을 대상으로 에니어그램 성격유형, 우울 및 불안과의 관계 (Lee, 2007), 에니어그램 성 격유형에 따른 의사소통 불안과 의사소통기술 수행의 차이 확인 (Park & Ha, 2014), 에니어그램 성격유형에 따른 건강증 진행위의 차이를 파악한 연구 (Kim, 2014)등이 있다. 그리고 대인돌봄행위 연구에서 간호대학생을 대상으로 정서지능과 대 인돌봄행위간에 유의한 상관관계 확인 (Peak, 2013), 대인돌봄 행위가 자아존중감과 정신건강, 희망, 삶의 질을 향상시키는 효과 확인 (Choi & Lee, 2010), 임상간호사의 대인돌봄 행위 수준 확인과 대인돌봄행위를 제공한 후의 효과 (Son, 2012) 연구의 구체적인 목적은 다음과 같다.…”
unclassified
“…In addition, findings are in contrast to another research [6] which studied gender difference in empathizing-systemizing traits in medical students and showed that cognitive empathy and the emotional response were significantly higher in the female students than in male students. In another study that compared communication skills [7], female students scored significantly higher than male students in "awareness", "comfort", and "acceptance". But in our study, direct comparisons with previous studies may be difficult because there are few papers comparing the communication skills of male and female nursing students with the objective evaluation of the instructor as done in this study.…”
Section: Discussionmentioning
confidence: 95%
“…This is almost 12-fold increase in the number [5]. The results from previous studies showed that female students scored higher in cognitive empathy and emotional response than male students [6] and in terms of communication skills, female students showed higher scores than male students in items including "awareness", "comfort", and "acceptance" [7]. Therefore, it is thought that there will a difference in the communication skills between female students and male students.…”
Section: Introductionmentioning
confidence: 97%